Яцишин Михайло Михайлович : біобібліогр. покажч. до 50-ти річчя від дня народження - Яцишин, Михайло Михайлович; Яцишин, Наталія Пилипівна; Сидорук, Інна Петрівна (Lesya Ukrainka Eastern European National University, 2018)
Біобібліографічний покажчик підготовлено до ювілею доктора юридичних наук, професора, завідувача кафедри теорії та історії держави і права Східноєвропейського національного університету імені Лесі Українки – Яцишина Михайла Михайловича. Уміщено бібліографію праць науковця, що охоплюють період від 1993 до 2018 рр., а також біографічна довідка. Видання доповнене допоміжними покажчиками. Бібліографічний опис видань оформлено згідно з чинними стандартами. Для наукових працівників, викладачів, аспірантів, студентів.

The bio-bibliographical index prepared to jubilee of the doctor of law, full professor, head of the theory and history of state and law department of Lesya Ukrainka Eastern European National University – Mykhailo Mykhailovych Yatsyshyn. The scientist’s papers are presented in the bibliographic order, covering the period from 1993 tо 2018, and biographical information. Auxiliary indexes are added to the edition. The bibliographical description of the publications is compiled in accordance with the valid standards. The book is appointed to scholars, teachers, post-graduates, students.
Keywords: bio-bibliographical index; Yatsyshyn Mykhailo Mykhailovych; Lesya Ukrainka Eastern European National University